Survey of intrusion detection techniques and architectures in cloud computing. (2019) - Sharma, Pinki; Sengupta, Jyotsna; Suri, P.K.
Cloud computing yields more utilisation of resources and hence a reasonable service access cost to end users. Cloud computing, virtually and dynamically, provides the data resources to a variety of users. As cloud computing is a shared facility, it is vulnerable to various attacks. The cloud networks have their own features which are the reason for threats to the security in clouds. The best solution to protect the cloud from the attacks is use of intrusion detection systems (IDS). This system is a better solution to achieve higher level of security, and is the most widely used technique where the system consists of IDS connected over the network in combination with various anomaly detection techniques. This paper provides an extensive survey of various cloud-based IDS architectures implemented in cloud environments for dealing with various security issues.